Does the length of intubation affect the success of treatment for congenital nasolacrimal duct obstruction? - Komínek, Pavel; Cervenka, Stanislav; Matousek, Petr (Ophthalmic plastic and reconstructive surgery, 2010)
PURPOSE: To compare success rates of intubation for 2 versus 5 months in congenital nasolacrimal duct obstruction in children between 15 and 30 months of age. METHODS: This prospective, randomized study evaluated drainage function in 145 eyes of children aged between 15 and 30 months and treated for congenital nasolacrimal duct obstruction using silicone stents with the fluorescein dye disappearance test. The tubes were removed 2 months (group I, 48 eyes) and 5 months (group II, 47 eyes) after stent placement. Thereafter, the children were followed for 6 months after tube removal. Fifty eyes were excluded from the study because of incomplete follow-up. RESULTS: The full resolution of symptoms (fluorescein test 0-1) was 33 of 48 in group I and 33 of 47 in group II at the time of tube removal (2 vs. 5 months). Six months after tube removal, the success rate was 43 of 48 (89.6%) in group I and 43 of 47 (91.5%) in group II. After the stents were removed, no relapses were observed in children having a fluorescein test 0-1 with the tubes remaining in the lacrimal system. CONCLUSIONS: The effects of intubation for 2 versus 5 months on the function of the nasolacrimal duct during and after intubation in children between 15 and 30 months of age are comparable. The fluorescein dye disappearance test is the test of choice for monitoring lacrimal drainage function.
Keywords: Fluorescent Dyes; Infant; předškolní dítě; výsledek terapie; Time Factors; časové faktory; lidé; ductus nasolacrimalis; fluorescein; Treatment Outcome; fluorescenční barviva; silikony; Nasolacrimal Duct; Fluorescein; prospektivní studie; kojenec; Prospective Studies; Stents; Child, Preschool; intubace; Silicones; obstrukce slzovodu; Lacrimal Duct Obstruction; Intubation; stenty; Humans